2017
DOI: 10.1007/s13187-017-1268-6
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in HPV-related Knowledge, Attitudes, and Beliefs Among African American and White Women in the USA

Abstract: The objective of this study was to assess the differences in HPV-related knowledge, attitudes, and beliefs among African American and non-Hispanic white women and to determine their communication preferences for cancer-related information. Data was obtained from the National Cancer Institute's (NCI) 2014 Health Interview National Trends Survey (HINTS), a cross-sectional survey of US adults 18 years of age or older. Descriptive statistics, bivariate, and multivariate logistic regression were used to identify di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
2
32
0
1
Order By: Relevance
“…Inclusion of community figures who are not medical authorities may be particularly useful in vaccination campaigns for reaching parents who are more vaccine hesitant given that vaccine hesitant parents and refusers may have lower levels of trust in, and more negative experiences with the medical system. [28][29][30] Our study suggests that like parents of other races, 10,31,32 African American parents trust medical authorities for vaccine advice. Nonetheless, qualitative studies have repeatedly demonstrated that though this may be true, African Americans' attitudes toward vaccination are multi-faceted and often impacted by deep-seated fears of experimentation.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Inclusion of community figures who are not medical authorities may be particularly useful in vaccination campaigns for reaching parents who are more vaccine hesitant given that vaccine hesitant parents and refusers may have lower levels of trust in, and more negative experiences with the medical system. [28][29][30] Our study suggests that like parents of other races, 10,31,32 African American parents trust medical authorities for vaccine advice. Nonetheless, qualitative studies have repeatedly demonstrated that though this may be true, African Americans' attitudes toward vaccination are multi-faceted and often impacted by deep-seated fears of experimentation.…”
Section: Discussionmentioning
confidence: 73%
“…Finally, similar to other surveys, trust in community figures for vaccine advice was assessed using a single item. 31,40,41 Future studies whose aim is to fine tune the assessment of trust in vaccine advisors may develop and test a scale to possibly assess this construct more precisely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In information and awareness studies on HPV and the HPV vaccine that were conducted in developed countries, it was reported that HPV knowledge and awareness were at low-tomoderate levels, and vaccination rates (26%-55%) were not at desired levels, although the willingness for vaccination was high (17,(28)(29)(30)(31)(32)(33)(34). In studies conducted in developing countries, it was reported that HPV knowledge and awareness and willingness for vaccination were at low-to-moderate levels, and HPV vaccination rates were quite low (13.3%-16.1%) (35)(36)(37)(38)(39)(40)(41).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Although HPV immunization willingness was high, various barriers made it difficult to raise vaccination rates to the desired level. HPV vaccination barriers in developed countries were listed as doubts about vaccine safety and efficiency, adverse effect concerns, lack or inconsistency of information about HPV and the HPV vaccine, and the price of the HPV vaccine (29,32,34). In developing countries, HPV vaccine barriers were the lack of awareness of the vaccine, doubting the safety and efficiency of the vaccine, finding it embarrassing to buy the vaccine for sexually transmitted infections, and people thinking that they were not at risk for HPV (35,37,41).…”
Section: Summary Of Evidencementioning
confidence: 99%